2019
DOI: 10.1093/eurheartj/ehz745.0006
|View full text |Cite
|
Sign up to set email alerts
|

3039Vulnerability of carotid atherosclerosis: relationship with plaque location, plaque eccentricity and vessel remodeling patterns. Insight from the the MAGNETIC observational study

Abstract: Carotid atherosclerosis is a cause of brain ischemic events. Cardiovascular magnetic resonance (CMR) can assess plaque vulnerability. We investigated atherosclerosis vulnerability in relation to plaque location, eccentricity and vessel remodeling. Methods-Baseline CMR evaluations of the MAGNETIC observational study, were analyzed. We quantitated with MRI-Plaque View™, vessel lumen/wall and vulnerable plaque components of a 32-mm segment of common carotid artery (12 mm), bulb (8 mm) and internal carotid artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…6). The eccentricity increases the biomechanical stress to the plaque by determining an increased vulnerability [108] and it was found that it is associated with an increased prevalence of IPH [109]. Initially, positive remodeling was believed to be a protective phenomenon [110], but newer pieces of evidence have demonstrated that it should be considered a parameter of vulnerability [111].…”
Section: Arterial Remodelingmentioning
confidence: 99%
“…6). The eccentricity increases the biomechanical stress to the plaque by determining an increased vulnerability [108] and it was found that it is associated with an increased prevalence of IPH [109]. Initially, positive remodeling was believed to be a protective phenomenon [110], but newer pieces of evidence have demonstrated that it should be considered a parameter of vulnerability [111].…”
Section: Arterial Remodelingmentioning
confidence: 99%